Bipolar endoscopic enucleation versus bipolar transurethral resection of the prostate: an ESUT systematic review and cumulative analysis - Arcaniolo, Davide; Manfredi, Celeste; Veccia, Alessandro; Herrmann, Thomas R. W.; Lima, Estevão; Mirone, Vincenzo; Fusco, Ferdinando; Fiori, Cristian; Antonelli, Alessandro; Rassweiler, Jens; Liatsikos, Evangelos; Porpiglia, Francesco; et al. (World journal of urology, 2020)
Purpose: To perform a cumulative analysis of the current evidence on the surgical and functional outcomes of bipolar endoscopic enucleation of the prostate (b-EEP) versus bipolar transurethral resection of the prostate (b-TURP). Methods: A systematic review of the literature was performed on PubMed, Ovid(R), and Scopus(R) according to Preferred Reporting Items for Systematic Review and Meta-analysis Statement (PRISMA Statement). The meta-analysis was conducted using the Review Manager 5.3 software. Parameters of interest were surgical and functional outcomes. Weighted mean difference, and odds ratio with 95% confidence interval were calculated for continuous and binary variables, respectively. Pooled estimates were calculated using the random-effect model. Results: Fourteen comparative studies were included. No statistically significant difference in terms of overall baseline characteristics was found. b-EEP had higher amount of resected tissue (p < 0.0001), shorter catheter time (p = 0.006), lower Hb drop (p = 0.03), and shorter length of stay (p < 0.0001). Equally, overall post-operative complications were lower (p = 0.01) as well as short (p = 0.04), and long-term complication rate (p = 0.04). There was higher re-intervention rate in the b-TURP group (p = 0.02) whereas b-EEP group had smaller residual prostate volume (p = 0.03), and lower post-operative PSA values (p < 0.00001). At long term, b-EEP presented lower IPSS (p = 0.04), higher Q(max) (p = 0.002), and lower PVR (p < 0.00001). Conclusions: b-EEP is an effective and safe surgical treatment for BPO. This procedure might offer several advantages over standard b-TURP, including the resection of a larger amount of tissue within the same operative time, shorter hospitalization, lower risk of complications, and lower re-intervention rate. This was submitted to PROSPERO registry: CRD42019126748.
Published online: 25 July 2019
Gesehen am 02.04.2020